Cranberry Juice Phytochemicals Attenuated Ethanol-Induce Epithelial Barrier Dysfunction on Caco-2 Monolayers (P06-094-19). (13th June 2019) - Gu, Liwei; Wang, Guang; Li, Ruiqi; Feng, Ye; Qian, Yu
Abstract: Objectives: The objective of this study was to determine whether cranberry juice phytochemicals protect intestinal barrier using Caco-2 monolayer models, and to elucidate the underlying mechanisms of cranberry juice phytochemicals on ethanol-induced barrier dysfunction. Methods: Cranberry juice phytochemicals were extracted using Amberlite FPX66 resin and phytochemicals composition were analyzed on HPLC. Caco-2 monolayers were incubated with cranberry juice phytochemicals at different concentrations for 2 hours before treatment with 4.5% ethanol. The transepithelial electrical resistance (TEER) and fluorescein isothiocyanate-labeled dextran (FITC) was used to evaluate paracellular permeability. Epithelial integrity and distribution of tight junction proteins (Occludin and ZO-1) in Caco-2 monolayers were determined by immunofluorescence labeling method. Protein levels of ZO-1, Occludin and Claudin-1 were determined by immunoblotting. Results: Cranberry juice phytochemicals consisted of malvidin 3, 5-diglucoside, petunidin 3-glucoside, chlorogenic acid and caffeic acid. Ethanol induced decrease of TEER while pretreatment of cranberry juice phytochemicals protected Caco-2 monolayer integrity in a dose-dependent manner. Monolayers treated with 7.5, 15, and 30 μg/mL of cranberry juice phytochemicals had TEER value 11.6%, 22.7% and 30.5% higher than the ethanol-treatment monolayers, respectively. This was accompanied by 40%, 55%, and 50% decreases of the paracellular permeability compared to ethanol-treated monolayers. Immunofluorescent analysis showed that occludin was localized tightly around cell membrane and colocalize with ZO-1 in the normal Caco-2 monolayers. Exposure to 4.5% ethanol disrupted both occludin and ZO-1 networks and resulted in gap formation among the cells. Cranberry juice phytochemicals attenuated these changes induced by ethanol exposure. Ethanol exposure significantly reduced the protein levels of occludin and ZO-1. Pretreatment with cranberry juice phytochemicals increased the protein levels of occludin dose dependently but did not affect ZO-1 level. Conclusions: Current study suggested that cranberry juices phytochemicals attenuate ethanol-induced intestinal barrier dysfunction in part by enhancing the tight junction assemblies. Funding Sources: NA.